The Effectiveness of the Port Knocking Method in Computer Security - Muhammad Nur; Teguh; Wasis Waskito; Azhar Fathoni; Bagas; Yuda; Ramadan Galih; Alif Ainnun Qoyum; Samsoni (PT FORMOSA CENDEKIA GLOBAL, 2023)
Computer network is a group of autonomous computers that are interconnected with each other using communication protocols through communication media so that they can share information, programs, share hardware devices such as printers, hard disks, and so on. One of the most important network components is network security, computer security involves various aspects, including protection against unauthorized access, data theft, system tampering, and operational disruptions. This research method uses descriptive method. At this stage specifications are determined regarding the system that will be designed to meet the objectives of this study, the Port Knocking method to secure the Router can be applied to Mikrotik routers by utilizing a firewall which functions to guard against illegal access and overcome problems caused by Attackers